Concussion knowledge, attitudes and behaviours among australian taekwondo athletes: a cross-sectional exploratory study - Brown, D. A.; Whitting, J.; Crowley-McHattan, Z.; Climstein, M.; Del Vecchio, L. (Sports, 2025)
Background: Sport-related concussion (SRC) is a recognised public health concern, with combat sport athletes particularly vulnerable due to frequent head impacts. In Taekwondo, concussion incidence is comparable to other contact sports, yet underreporting and misconceptions may hinder safe management. Understanding knowledge, attitudes, and behaviours in this cohort is critical for athlete safety.